Islamic Economic Literacy: A Paradigma Economic Thought In Indonesia - Ahmad Lukman Nugraha; Sofian Al Hakim; Dedah Jubaedah; Antoni Julian; Mohamad Anton Athoillah (Journal of Islamic Economics and Philanthropy, 2023)
The author aims to find out the relationship between Islamic economic philosophy and developing economic ideology. The author tries to put forward the relationship between Islamic economic philosophy and the Pancasila ideology as the foundation of the nation. The method research used descriptive qualitative method by a literature study and a normative phisopic. The results of the analysis of this paper suggest that the post-sila economy has aspects in common with the principles of Islamic economic values, namely; the first precept with at-Tawhid, the second with al 'Adalah, the third precept with Ukhuwwah, the fourth precept with Musywarah and the fifth precept with Falah.